The beneficial effect of probiotics in the prevention of irinotecan-induced diarrhea in colorectal cancer patients with colostomy: a pooled analysis of two probiotic trials (Probio-SK-003 and Probio-SK-005) led by Slovak Cooperative Oncology Group - Mego, Michal; Kasperova, Barbora; Chovanec, Jozef; Danis, Radoslav; Reckova, Maria; Bystricky, Branislav; Konkolovsky, Peter; Jurisova, Silvia; Porsok, Stefan; Vaclav, Vladimir; Wagnerova, Maria; Stresko, Marian; et al. (Frontiers in Oncology, 2024)
Background Probiotics could decrease irinotecan-induced diarrhea due to the reduction of intestinal beta-d-glucuronidase activity. This study included a combined analysis of two clinical trials aimed to determine the effectiveness of the probiotics in the prophylaxis of irinotecan-induced diarrhea in metastatic colorectal cancer (CRC) patients. Methods This combined analysis included 46 patients with CRC enrolled in the Probio-SK-003 (NCT01410955) and 233 patients from Probio-SK-005 (NCT02819960) starting a new line of irinotecan-based therapy with identical eligibility criteria. Patients were randomized in a ratio 1:1 to probiotic formulas vs. placebo administered for 12 and 6 weeks, respectively. Due to the different durations of study treatments, only the first 6 weeks of therapy were used for analysis. Results In total, 279 patients were randomized, including 142 patients in the placebo and 137 participants in the probiotic arm. Administration of probiotics did not significantly reduce the incidence of grade 3/4 diarrhea compared to placebo (placebo 12.7% vs. probiotics 6.6%, p = 0.11). Neither the overall incidence of diarrhea (placebo 48.6% vs. probiotics 41.6%, p = 0.28) nor the incidence of enterocolitis (placebo 4.2% vs. probiotics 0.7%, p = 0.12) was different in the placebo vs. probiotic arm. However, subgroup analysis revealed that patients with a colostomy who received a placebo had a significantly higher incidence of any diarrhea (placebo 51.2% vs. probiotics 25.7%, p = 0.028) and grade 3/4 diarrhea (placebo 14.6% vs. probiotics 0.0%, p = 0.03) compared to the probiotic arm. Conclusions This combined analysis suggests that probiotics could be beneficial in the prevention of irinotecan-induced diarrhea in colorectal cancer patients with colostomy.